Reinfection or relapse? A case study of whole genome sequencing guided genomic characterization of Mycobacterium abscessus chronic infection in a cystic fibrosis patient. (2022) - Chawla, Rachit; von Bredow, Benjamin; Deville, Jaime; Yang, Shangxin
Abstract: A 7-year-old cystic fibrosis patient with increased cough, new pulmonary infiltrate, and declining pulmonary function was diagnosed with clarithromycin resistant Mycobacterium abscessus infection. Treatment was initiated with clofazimine, linezolid and cefoxitin; she responded well to therapy and achieved microbiological clearance after completion of 12-month treatment. One year later, she had re-emergence of worsening symptoms and her sputum culture again grew clarithromycin resistant M. abscessus . Using a laboratory developed whole genome sequencing (WGS) test, the bacterium was determined to be the same strain with the same resistance mechanisms, indicating a relapse. This was deemed a critical element of clinical information, as the isolation of a genetically distinct organism would have indicated a new infection and would have served as evidence that a 12-month regimen was likely sufficient to achieve eradication. The confirmation of a relapse prompted the prolongation of the therapy plan to a goal of 24 months. Reinfection and relapse are great challenges in patients with cystic fibrosis who may acquire new strain of M. abscessus from the environment, may harbor multiple subpopulations of bacteria, or may have persistent infections but intermittent bacteria shedding that could not be eradicated. WGS has emerged as a powerful molecular tool to accurately differentiate re-infection from relapse thus solving this conundrum. Highlights: ▪ Recurrent M. abscessus infections are great challenges in cystic fibrosis patients. ▪ WGS enables high-resolution phylogenetic comparison of M. abscessus differentiating re-infection from relapse. ▪ Differentiating re-infection from relapse can be useful in managing recurrences of M. abscessus infections.